Respostas

A melhor resposta!
2013-08-28T17:52:35-03:00
01) 3x² - 2(x² - 1) = 2
3x² - 2x² + 2 = 2
x² = 2 - 2
x² = 0
x = √o
x = 0

02) 5x² - 3(x² - 1) = 6 - 3x
5x² - 3x² + 3 = 6 - 3x
2x² + 3x - 3 = 0

Δ = 3² - 4.2.(-3)

Δ = 9 + 24
Δ = 33

x = -3 +/- √33 / 2.2 = -3 +/- √33 / 4
x' = -3 + √33 / 4
x'' = -3 - √33 / 4

03) 9x² - 5(x - x²) = 2x 
9x² - 5x + 5x² = 2x
14x² - 7x = 0

Δ = (-7)² - 4.14.0
Δ = 49

x = -(-7) +/- √49 / 2.14 = 7 +/- 7 / 28
x' = 7 + 7 / 28 = 14/28 :14 = 1/14
x'' = 7 - 7 / 28 = 0/28 = 0

04) (x + 2)² = 4x + 5 
(x² + 2.x.2 + 2²) = 4x + 5
x² + 4x + 4 = 4x + 5
x² = 5 - 4
x² = 1
x = 
√1
x = 1

05) (2x + 3)² = (x - 3)²
(2x)² + 2.2x.3 + 3²) = (x² + 2.x.(-3) + (-3)²)
4x² + 12x + 9 = x² - 6x + 9
3x² + 18x = 0

Δ = 18² - 4.3.0
Δ = 324

x = -18 +/- √324 / 2.3 = -18 +/- 18 / 6
x' = -18 + 18 / 6 = 0/6 = 0
x'' = -18 - 18 / 6 = -36/6 = -6

":" -> significa "simplificado por"
1 5 1